Amygdala-frontal couplings characterizing SSRI and placebo response in social anxiety disorder. (August 2014) - Faria, Vanda; Åhs, Fredrik; Appel, Lieuwe; Linnman, Clas; Bani, Massimo; Bettica, Paolo; Pich, Emilio Merlo; Fredrikson, Mats; Furmark, Tomas
Abstract In patients with social anxiety disorder (SAD) it has been reported that selective serotonin reuptake inhibitors (SSRIs) and placebo induce anxiolytic effects by attenuating neural activity in overlapping amygdala subregions, i.e. left basolateral and right ventrolateral amygdala. However, it is not known whether these treatments inhibit amygdala subregions via similar or distinct brain pathways. As anxiolytic treatments may alter amygdala-frontal couplings we investigated differences and similarities in amygdala-frontal functional co-activation patterns between responders and nonresponders to SSRIs and placebo in patients with SAD. Positron emission tomography (PET) with oxygen-15-labeled water was used to measure anxiety-related regional cerebral blood flow in 72 patients with SAD before and after 6–8 wk of treatment under double-blind conditions. Functional couplings were evaluated with a seed region approach using voxel values from the left basolateral and right ventrolateral amygdala. Responders and nonresponders to SSRIs and placebo showed different treatment-induced co-activations between the left amygdala and the dorsolateral prefrontal cortex (dlPFC) as well as the rostral anterior cingulate cortex (ACC). Conjunction analysis suggested shared anxiolysis-dependent inverse co-activations in SSRI and placebo responders between the left amygdala-dlPFC and left amygdala-rostral ACC, and a shared positive co-activation between left amygdala-dorsal ACC. We demonstrate that amygdala-frontal co-activation patterns differentiate effective from ineffective anxiolytic treatments and that SSRI and placebo responders share overlapping neuromodulatory paths that may underlie improved emotion regulation and reduced expression of anxiety. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT00343707.